Fiscal Dependency of Karnataka - Rumana Fathima, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Revenue adequacy refers to the availability of a sufficient level of revenue to finance essential public services. The objective of this study is to examine the changing trends in the composition of total revenue receipts of Karnataka. Covering the period from 2011–12 to 2023–24, the analysis focuses on Karnataka’s fiscal autonomy and its dependency on various components of transfers. To examine compositional shifts and growth patterns in the total revenue receipts comprising own tax revenue, non-tax revenue, share in central taxes and grants, it employs descriptive statistics, Coefficient of Variation, Annual Average Growth Rate, and Compound Annual Growth Rate. It is evident from the analysis of CAGR and AAGR that, growth of total revenue receipts displayed a steady long-term expansion, with an AAGR of 6.42% and a CAGR of 6.15%. Within this, own source revenue has recorded an AAGR of 5.82% and a CAGR of 5.66%, reflecting stable but moderate growth, largely driven by SGST, excise, and stamp duty. In contrast, intergovernmental transfers grew more rapidly, with an AAGR of 8.18% and a CAGR of 7.36%, indicating increasing reliance on central transfers. Among the two major components of transfers, the share in central taxes an AAGR of 8.25% but a lower CAGR of 5.68%, due to volatility during the early years of GST implementation and disruptions caused by COVID-19. Grants from the Centre exhibited the highest growth, with an AAGR of 11.16% and a CAGR of 9.28%, though their unstable and conditional nature makes them an unreliable revenue source. Overall, own source revenue has remained as most stable source of revenue. However, Karnataka’s recent revenue growth has been driven largely by central transfers and grants, highlighting structural dependence despite a strong internal revenue base. The evidence suggests that, despite stronger fiscal self-reliance, Karnataka continues to relay on intergovernmental transfers to sustain revenue growth.
Keywords: Fiscal Dependency; Own Source Revenue (OSR); Intergovernmental Transfers (IGT); Revenue Adequacy; Compound Annual Growth Rate (CAGR)